Targeting Rac and Cdc42 GTPases in Cancer - del Mar Maldonado, María (Cancer Res, 2018)
Rac and Cdc42 are small GTPases that have been linked to multiple human cancers, and implicated in epithelial to mesenchymal transition, cell cycle progression, migration/invasion, tumor growth, angiogenesis, and oncogenic transformation. With the exception of the P29S driver mutation in melanoma, Rac and Cdc42 are not generally mutated in cancer, but are overexpressed (gene amplification and mRNA upregulation) or hyperactivated. Rac and Cdc42 are hyperactivated via signaling through oncogenic cell surface receptors, such as growth factor receptors, which converge on the guanine nucleotide exchange factors (GEFs) that regulate their GDP/GTP exchange. Hence, targeting Rac and Cdc42 represent a promising strategy for precise cancer therapy, as well as for inhibition of bypass signaling that promotes resistance to cell surface receptor-targeted therapies. Therefore, an understanding of the regulatory mechanisms of these pivotal signaling intermediates is key for the development of effective inhibitors. In this review, we focus on the role of Rac and Cdc42 in cancer and summarize the regulatory mechanisms, inhibitory efficacy, and the anticancer potential of Rac and Cdc42 targeting agents.